Enhancing Biomass-Exopolysaccharides Production of Lignosus rhinocerus in a High-Scale Stirred-Tank Bioreactor and Its Potential Lipid as Bioenergy - Siti Rokhiyah Ahmad Usuldin; Zul Ilham; Adi Ainurzaman Jamaludin; Rahayu Ahmad; Wan Abd Al Qadr Imad Wan-Mohtar (Energies, 2023)
The depletion of fossil fuels and the emission of greenhouse gases have increased the demand for new and sustainable energy sources, leading to growing interest in using fast-growing filamentous fungi as a source of bioenergy. This study aimed to optimize the production of exopolysaccharides (EPS) and mycelial biomass (MB) from the native medicinal mushroom, Lignosus rhinocerus, through submerged liquid fermentation. Using response surface methodology (RSM), it was found that the glucose concentration and speed of agitation significantly influenced the production of MB and EPS (p < 0.05), while the initial pH medium had an insignificant effect. The validated optimized parameters of 50.0 g/L glucose, initial pH 4.0, and 128 rpm for speed of agitation were tested in 500 mL shake flasks, 5 L, and 13 L stirred-tank (STR) bioreactors. The production of MB and EPS increased significantly by ~1.2-fold in the 5 L STR and further increased to ~1.7-fold (MB) and ~2.4-fold (EPS) in the 13 L STR bioreactor compared to the shake flask. The lipid content of MB was also determined, with a result of 2.07% w/w using the Soxhlet extraction method. To conclude, this study emphasizes the ability of L. rhinocerus as a new source of bioenergy through large-scale production, with optimized parameters serving as a reference for future research and practical applications.